If you're so smart, why aren't you happy? - Raghunathan, Raj (Portfolio/Penguin, 2016)
"Fifteen years after getting his MBA, Raj Raghunathan spent some time with his old classmates. He noticed that though they'd all done well, there didn't appear to be much correlation between their academic success and career success. What Raghunathan found even more curious was the even smaller correlation between career success and what he calls life success. The greater the career success, the more unhappy, out of shape, harried, and distracted his friends were."--Book jacket.